THE EFFECT OF BASIC LIFE ASSISTANCE TRAINING (BHD) ON MOTIVATION AND DEMEANOUR OF CLASS XI STUDENTS IN RESCUING TRAFFIC ACCIDENTS IN SMA NEGERI 2 TENGGARONG - Alfi Ari Fakhrur Rizal; Indah Nur Imamah; Milkhatun Milkhatun (Jurnal Ilmu Kesehatan, 2019)
Traffic accidents are one of the public health problems that affect all sectors of life. The phenomenon of traffic accidents so far has not received much public attention as a cause of death. The increase in mortality rates that occur on the highway is very high and quite a concern and vigilance for the community. This usually happens one of them because the Indonesian people do not know how to help victims who are good and right when finding victims. As a result most of actions is wrong, so it can add to injury and death. This study aims to determine the effect of basic life support (BLS) training on the motivation and demeanour of class XI students in rescuing traffic accidents in SMA Negeri 2 Tenggarong. This study uses a quasy experimental method of pre and post design with a control group. Proportional stratified random sampling technique with a sample of 78 students and data collection using a questionnaire sheet. Data that was analyzed by paired t test in each group showed a p-value of 0,000 <0.05, meaning that there was a statistically change in motivation and attitude between before and after treatment in the form of BLS training for class XI students at SMAN 2 Tenggarong. The result is not much different from the independent t test which showed p-value 0,000 <0.05, which means there is a statistically different demeanour between the difference before and after treatment in the form of BLS training in the control and intervention groups. The results showed that there was a statistically significant change in motivation and demeanour between before and after the BLS training was given to the motivation and demeanour of class XI students at SMAN 2 Tenggarong with a p-value of 0,000 <0.05.